Quizzy as a Digital Diagnostic Assessment Instrument In Primary Education - Safril Abidin Hasibuan; Inayatus Saadah Dalimunthe; Tiapisah Samosir; Rama Nida Siregar (International Journal of Community Service (IJCS), 2026)
Diagnostic assessment is an important part of the implementation of the Independent Curriculum because it functions to identify the initial abilities, learning needs, and characteristics of students before the learning process is implemented. However, the implementation of diagnostic assessments in elementary schools still faces various obstacles, such as the limitations of interactive, efficient, and easy-to-analyze instruments. This article aims to examine the use of Quizzy as a digital diagnostic assessment instrument in primary education. The research uses a systematic literature review method with a qualitative descriptive approach through searching for accredited scientific articles on Google Scholar, SINTA, and Garuda published in the 2021–2025 range. The results of the study show that Quizzy has significant potential in supporting cognitive and non-cognitive diagnostic assessments through gamification features, instant feedback, and automated data analytics that make it easier for teachers to map students' learning abilities and needs. In addition to increasing the effectiveness of diagnostic data collection, the use of Quizzy is also able to increase the motivation, participation, and active involvement of elementary school students during the assessment process. However, the implementation of Quizzy still faces challenges in the form of limited technology infrastructure and teachers' digital competencies. Therefore, support for training and the development of digital facilities is needed so that the use of Quizzy as a diagnostic assessment instrument can run optimally in elementary schools.